Synthesis of Dihydropyrimidine Derivatives by Biginelli's Reaction in student Workshops on Organic Chemistry - Simurova, Natalia; Kovaleva, Svetlana; Mazur, Larisa (My University, 2017)
In classical student workshops, the attention paid to the synthesis of heterocyclic compounds is very little. This is due to the complexity and duration of most of these syntheses, the low availability of the initial reagents, the difficult isolation and purification the reaction products. Biginelli's reaction, as a method of synthesis of dihydropyrimidones, is attractive to be used in the student workshop on chemistry due to the simple procedure of synthesis, as well as a possibility to vary the reaction conditions and select initial reagents to introduce substituents that may be easily transformed to various functional groups.. Students cannot only get acquainted with the basic experimental methods, but also learn how to apply theoretical knowledge in practice, including monitoring of reactions and analyzing organic compounds by physico-chemical methods.
Keywords: дігідропіримідон; студентський практикум; реакція Біджинеллі; мультикомпонентні реакції; гетероцикл; дигидропиримидон; студенческий практикум; реакция Биджинелли; мультикомпонентные реакции; dihydropyrimidone; student workshop; Biginelly reaction; multiple-component reaction; heterocycle; кафедра харчової хімії